LITERATURE REVIEW: ANALYSIS OF WEAKNESS AND INHIBITING FACTORS IN THE IMPLEMENTATION OF THE MERDEKA CURRICULUM - Akbar, Muhammad; Putri, Noni Khaisha; Febriani, Sarah; Abunoya, Juleha Ilfri; Sukemi, Sukemi (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
The Merdeka Curriculum issued by the Ministry of Education, Culture, Research and Technology is expected to be a program that is able to overcome educational problems due to the Covid-19 Pandemic. This curriculum offers three functions, namely project-based learning characterized by the Pancasila Student Profile, study of subject matter and a more flexible curriculum structure. An application of the curriculum has weaknesses and inhibiting factors. This literacy study was conducted to examine the weaknesses and inhibiting factors in implementing the Merdeka Curriculum. The method used is a narrative literature review with a literature search using keywords in the range of 2019 to March 2023 and 30 relevant articles were found. Weaknesses and inhibiting factors found in the implementation of the Merdeka Curriculum, namely teacher unpreparedness, lack of training related to the Merdeka Curriculum, lack of facilities and infrastructure, and a less than optimal learning system. The results of this literature review indicate that it is necessary to analyze and evaluate the Merdeka Curriculum so that solutions are found and actions that can overcome weaknesses and inhibiting factors that ultimately it is hoped that the implementation of the Merdeka Curriculum can run well. Keywords: Pancasila Student Profile, Merdeka Curriculm, Inhibiting factor